รูปแบบพัฒนาการส่งสารภาษาไทยผ่านสื่ออิเล็กทรอนิกส์ ของนักศึกษาสาขาวิชาการสอนภาษาไทย ปีที่ 2 มมร วิทยาเขตล้านนา ปีการศึกษา 1/2561 - ปฏิภาณเมธี, พระณฐกร; (บุญชู สุดโสม), พระครูปริยัติกิตติวิมล; ชัยแสวง, อัครชัย; ภูลายยาว, กิตติคุณ; ศักด์วีระกุล, ทองสาย; พิมพ์คิรี, ชุ่ม (วารสาร ศึกษาศาสตร์ มมร, 2018)
บทคัดย่อ           งานวิจัยนี้มีวัตถุประสงค์ ดังนี้ 1.). เพื่อสร้างรูปแบบพัฒนาการส่งสารภาษาไทยผ่านสื่ออิเล็กทรอนิกส์  ของนักศึกษาสาขาวิชาการสอนภาษาไทยปีที่ 2   มมร วิทยาเขตล้านนา   ปีการศึกษา  1/2561 2.) เพื่อพัฒนารูปแบบการส่งสารภาษาไทยผ่านสื่ออิเล็กทรอนิกส์  ของนักศึกษาสาขาวิชาการสอนภาษาไทยปีที่ 2 มมร วิทยาเขตล้านนา ปีการศึกษา  1/2561 และ 3 เพื่อเปรียบเทียบความคิดเห็นการส่งสารของนักศึกษากลุ่มทดลองและกลุ่มควบคุม กลุ่มตัวอย่างที่ใช้ในการวิจัยคือ นักศึกษาที่กำลังเรียนอยู่ชั้นปีที่ 2  จำนวน 61 รูป เครื่องมือที่ใช้ได้แก่ แบบสอบถาม แบบสัมภาษณ์แบบมีโครงสร้าง แล้วนำเสนอผลการวิจัยในรูปแบบของการบรรยาย           ผลการวิจัยพบว่า โดยรวมแปลผลความคิดเห็นอยู่ในระดับมาก ด้านการใช้คำศัพท์ของนักศึกษาสรุปผลการเปรียบเทียบโดยรวมกลุ่มที่ทดลองหรือควบคุมด้วยการเรียนรู้แบบโยนิโสมนสิการคือ การรู้จักคิด พิจารณาก่อนการใช้คำศัพท์โดยมีค่าเฉลี่ยน้อยกว่ากลุ่มปกติเท่ากับ 2.91 (จาก3.67) และมีส่วนเบี่ยงเบนมาตรฐานเท่ากับ .88 ต่างจากกลุ่มปกติ .76 หน่วยความถี่  แสดงให้เห็นว่า นักศึกษากลุ่มทดลองมีความตระหนักในการใช้ภาษาดีกว่ากลุ่มปกติ รายด้านพบว่า ด้านกระบวนการในการฝึกตระหนักแบบโยนิโสมนสิการ ด้านความรู้ด้านความรู้ที่เป็นทักษะการส่งสารมีค่าความเห็นโดยรวมอยู่ในระดับมากและด้านการพัฒนาด้านการพัฒนาการฝึกทักษะการการส่งสารที่เป็นรูปแบบพัฒนาการส่งสารภาษาไทยผ่านสื่ออิเล็กทรอนิกส์ด้วยโยนิโสมนสิการมีค่าความเห็นโดยรวมอยู่ในระดับมาก ด้านข้อเสนอแนะพบว่า นักศึกษาได้แสดงปัญหาข้อเสนอแนะด้านคำศัพท์ เพิ่มเติมเช่น คำว่า เผือก หมายถึง ยุ่งเรื่องชาวบ้าน คำว่า สายเปย์  หมายถึง ชอบจ่ายให้ และ คำว่า หลัว  หมายถึง สามี  ข้อเสนอแนะด้านอื่น เช่น ควรใช้หลักธรรมอื่นๆ อีก ด้านกระบวนการ ฝึกความตระหนัก คือ ควรให้ฝึกการออกเสียงแบบ ด้านความรู้ที่เป็นทักษะในการส่งสาร      คือ ควรออกเสียงอ่านตามตัวอักษร และด้านการพัฒนาการฝึกทักษะการส่งสารว่า ควรเขียนด้วยอารมณ์ดี ส่วนด้านการสัมภาษณ์ พบว่า ด้านคำศัพท์  นักศึกษาทั้ง 6 เกิดความคิดหรือตระหนักได้ว่า ควรจักใช้คำศัพท์เช่นไรในการส่งสารแต่ละครั้งและคนหนึ่งได้กล่าวว่า จักพยายามใช้ให้ดีที่สุดและจักนำวิธีการใช้คำไปบอกกล่าวกับเพื่อนและญาติพี่น้องด้วย ABSTRACT The objective of this research is as follows  1) To create a model to develop Thai language transmission electronic media. Of students in the field of Thai language teaching, 2nd year, Lanna Campus, academic year 1/2561  2) To develop the Thai language transmission model electronic media Of students in the field of Thai language teaching, 2nd year, Lanna Campus, academic year 1/2561 and 3) to compare the opinions of the messenger of the experimental group and the control group The sample group used in the research was Students studying in the second year, number 61, tools used are questionnaires, structured interviews. And present the research results in the form of lectures            The research found that By including interpreting the results at a high level In terms of the vocabulary used by students, summarizing the results of the comparison by combining the experimental group or by using the Yonisomanasikarn learning method is the knowledge of thinking before using the vocabulary, with an average less than the normal group equal to 2.91 (from 3.67) and The standard deviation is .88. Unlike the normal group .76, the frequency unit shows that Students in the experimental group were aware of language usage better than the normal group. It was found that in the process of practicing Yonisomanasikarn awareness Knowledge of knowledge that is a communication skill has a high level of overall opinion and development in the development of the practice of communication skills that is a form of development of Thai language transmission via electronic media. Knicks with Yonisomanasikarn have a high level of overall opinion.                                          The suggestion that the course structure is should be In the suggestion, it was found that Students expressed problems with vocabulary suggestions. More like the word taro means busy with the villagers. The word "Saipe" means "like to pay" and "Lua" means "husband". Other suggestions, for example, should use other principles of the process. Awareness training is a way to practice pronunciation. The knowledge that is skills in the transmission is should be pronounced according to the letter. And development of communication skills Should write in a good mood As for the interview, it was found that in terms of vocabulary, all 6 students had thought or realized that What words should be used in each submission and one person said Will try to use the best and will use the words to tell friends and relatives as well